Psych pedagogical characterization of the rifle shooter´s special physical preparation (Review) (Revista científica Olimpia, 2020)
Preliminary studies on this research began with theoretical, practice and methodological insufficiencies accentuated on the way of adapting the psych pedagogical characteristics detected on the physical preparation process as an essential component in the athlete´s preparation. On this article we intent to achieve a psych pedagogical characterization during this process, starting with the psychological and pedagogical relationship on the matter. Observational elements are offered. The analysis about the processes that interact on this modality and are present during training as well as its organization on the pedagogy aspects are also boarded on this article. We begin with some criteria evidencing the study and reasoning of this preparation component, followed by the fundamental characteristics in the psych pedagogical order.   The investigative praxis was developed since 2017 with the riffle shooters on the 13-16 categories in the Sports Initiation School Pedro Batista Fonseca at our province, these athletes have a sport´s life average of two years of experience, research space, during we have proceed to define the psych pedagogical characteristics during the riffle shooters´ special physical preparation.
Keywords: special physical preparation, riffle shooters, psyches pedagogical, pedagogical, psychological.